Coverage of OpenStreetMap data at firm level : Assessing the suitability for social science representative firm samples and found - Gerhards, Christian [Verfasser] (My University, 2025)
"Establishment surveys are essential for gaining well-founded insights into company structures and developments, whereby representativeness ensures that the results can be reliably transferred to the population and enable bias-free conclusions. Company surveys in Germany are often based on the company file of the Federal Employment Agency (BA), which, however, only allows limited links to other data sources. The free online service OpenStreetMap (OSM) could serve as an alternative, publicly accessible data source. This article analyses the extent to which OSM is suitable for drawing a representative sample of companies. It is hypothesised that OSM covers a large proportion of businesses, especially in metropolitan areas, and that customer-oriented sectors are better covered than industrial or B2B businesses. To verify this, establishments are identified in OSM and compared with the BA establishment file, differentiated by region and sector. The results show a high but not complete coverage with regional differences in favour of metropolitan areas. There are limitations in terms of data quality and contactability of the establishments." (Author's abstract, BIBB-Doku)
Keywords: T 3 Forschungsmethoden; G 1.2.4 Wirtschaftszweige; I 2.1.4 Ballungsgebiete; 370; Datenanalyse; Stichprobenverfahren; Betriebsbefragung; Wirtschaftszweig; Ballungsraum